Information on Candidacy for the 36th Assembly District - Jane Tolmach:::::: (1976)
Information sent to Chuch Thomas, the editor of the Ventura County Star-Free Press, describing the positions that Jane Tolmach plans to take if elected. Includes edits made to the statement.